Grain size influence on the thermal properties of stabilized zirconia-nano spinel (Al2O3-MgO) composites - mohammad Almasi Kashi; Hafidh Yousif Abed; Shihab Ahmed Zaidan Ahmed Zaidan (Journal of Nanostructures, 2019)
Abstract. Cubic crystalline oxides such as Y2O3 and MgO is used to stabalized zirconia phases at high temperature. In this paper the Y2O3 powder was added to stabilized zirconia and preparing a mixture of MgAl2O4 Spinel by mixing 1mol of nano-MgO with 1 mol of nano-Al2O3 powders. The spinel was added to the Y2O3-ZrO2 by various weight percentage (5, 10, 15, 20 and 25 wt%), and after that the specimens was prepared by axial pressing and sintered at 1550 oC for 4 hours as soaking time. The grain size was tested by using Atomic Force Microscopy (AFM) and calculated for surface of specimens and it was found to be decreasing (> 0.6 µm) to (~ 108 nm). The thermal properties were clearly influenced by the structural characteristics of the MAS. The thermal conductivity and thermal diffusion was decreased slightly from 5.7 to 5.5 W/m.K and from 2.5 to 1.5 mm2/s, respectively. The thermal capacity was increased from 483 to 615 J/kg.K, and thermal expansion coefficient was increased from 10 to 7.510-6 oC-1 due to the compatibility of thermal expansion coefficients of (Y-PSZ)-MAS oxides. Thermal properties values are compatible with thermal insulation requirements in energy storage applications.